Gambaran Komunikasi Interpersonal Siswa Ditinjau dari Jenis Kelamin dan Implikasinya dalam Bimbingan dan Konseling - Matondi, Sari; Suhaili, Neviyarni (Lembaga Yasin AlSys, 2024)
This research is motivated by the existence of students who lack self-confidence when communicating with teachers and peers, because of their lack of self-confidence students are afraid and hesitant to speak and this can be an obstacle to communicating. Lack of skills when communicating such as listening, speaking clearly, and reading other people's expressions. This research aims to:describe the picture of student interpersonal communication, describe the picture of student interpersonal communication in terms of gender. This research uses a quantitative approach with comparative descriptive quantitative type. The population of this study consisted of 523 students and the research sample was 227 students with engineeringproportionate stratifiedrandom sampling. The instrument used is the interpersonal communication scale. Data were analyzed using descriptive techniques and to see differences using the t-test. The research results revealed that interpersonal communication among students was in the high category with an average achievement score of 52.86%.There is no significant difference in interpersonal communication between male and female students. The role of guidance and counseling teachers is very necessary to help develop students' interpersonal communication through information services, individual counseling services, and group guidance services for guidance and counseling teachers or school counselors in order to improve students' interpersonal communication.